Multitrophic diversity effects of network degradation. Issue 14 (21st June 2016) - Nichols, Elizabeth; Peres, Carlos A.; Hawes, Joseph E.; Naeem, Shahid
Abstract: Predicting the functional consequences of biodiversity loss in realistic, multitrophic communities remains a challenge. No existing biodiversity–ecosystem function study to date has simultaneously incorporated information on species traits, network topology, and extinction across multiple trophic levels, while all three factors are independently understood as critical drivers of post‐extinction network structure and function. We fill this gap by comparing the functional consequences of simulated species loss both within (monotrophic) and across (bitrophic) trophic levels, in an ecological interaction network estimated from spatially explicit field data on tropical fecal detritus producer and consumers (mammals and dung beetles). We simulated trait‐ordered beetle and mammal extinction separately (monotrophic extinction) and the coextinction of beetles following mammal loss (bitrophic extinction), according to network structure. We also compared the diversity effects of bitrophic extinction models using a standard monotrophic function (the daily production or consumption of fecal detritus) and a unique bitrophic functional metric (the proportion of daily detritus production that is consumed). We found similar mono‐ and bitrophic diversity effects, regardless of which species traits were used to drive extinctions, yet divergent predictions when different measures of function were used. The inclusion of information on network structure had little apparent effect on the qualitative relationship between diversity and function. These results contribute to our growing understanding of the functional consequences of biodiversity from real systems and underscore the importance of species traits and realistic functional metrics to assessments of the ecosystem impacts of network degradation through species loss. Abstract : Predicting the functional consequences of biodiversity loss in real communities remains a challenge. Growing evidence points to the importance of including information on multiple trophic levels, trait‐ordered species decline, and network structure into diversity effect models, as well as the importance of incorporating realistic measures of ecological function, to to our knowledge no study to date has combined all four components simultaneously to explore the functional consequences of multi‐trophic species loss. We contrasted the predicted functional consequences of species loss both within (mono‐trophic) and across (bi‐trophic) a foodweb of fecal detritus producer and consumers (tropical forest mammals and dung beetles) and found that while both mono and bi‐trophic extinction scenarios demonstrated similar diversity effects, different ways of measuring function can dramatically influence results.